On the laminar region and the initial stages of transition in transitional separation bubbles - Serna, J.; Lázaro, B.J. (European journal of mechanics, B, Fluids, 2015)
Separated transitional boundary layer flows exhibit a laminar region after separation. The momentum thickness and the distance to the wall of the separated shear layer are the key parameters controlling the instability process that promotes transition and the reattachment of the flow. This work proposes scaling laws for the defining parameters of this shear layer: its angle with the wall, its length, and the momentum thickness evolution. The laws are supported by experimental measurements performed in a boundary layer that develops over a flat plate, subject to an adverse pressure gradient such that in the inviscid limit the velocity over the plate decreases linearly along its length. The flow Reynolds number based on the characteristic boundary layer edge velocity and deceleration length takes values in the 105–106 range. The edge velocity and the momentum thickness along the separated shear layer are found to be almost constant. Furthermore, the layer is seen to separate from the wall with the appropriate angle to compensate the externally imposed adverse pressure gradient, and a relationship between its length and angle is found. Additionally, a comparison between Linear Stability Theory for parallel flows and hot-wire velocity spectral measurements performed in the separated shear layer is presented. A good agreement between the most unstable frequencies and amplification rates predicted by this theory and the ones experimentally measured is found. The hypothesis of a Kelvin–Helmholtz like instability (inviscid or inflectional instability) triggering the instability process is also reinforced as a result.